Cruelty : human evil and the human brain - Taylor, Kathleen E. (Kathleen Eleanor) (Oxford University Press, 2009)
"Cruelty is an uncomfortable subject. Reading of the horrors of the Nazi death camps and the genocides of Rwanda, seeing news reports of young children being beaten and starved to death, we are repelled and horrified. The people doing these acts must surely be evil monsters, utterly different from ourselves." "But is it really so simple? In this lucid and thought-provoking analysis, Kathleen Taylor points out that cruelty is as much part of our human makeup as love and kindness. Everyone of us is capable of being cruel, to varying extents, in certain circumstances. Taylor explores the nature of callous and sadistic cruelty, showing how they are driven by emotions and beliefs, often under conditions of stress and time pressure." "Our responses to the world come from our brain - in Taylor's words. 'the soggy, fatty mass from which cruelty is born'. Can neuroscience shed any light on the phenomenon of cruelty? Yes it can, says Taylor, and we should draw on our growing understanding of the nature of emotion and beliefs, and of how patterns of behavior are formed and reinforced, in any analysis of cruelty. For cruelty is not incomprehensible, though that too is an uncomfortable thought. It is accessible to analysis. And it is only by understanding this most disturbing aspect of the human psyche that we can attempt to reduce it and avoid the circumstances in which it tends to arise."--BOOK JACKET.